EFFECT OF PHYTOECDYSTEROIDS ON ENZYMES OF THE INITIAL AND FINAL STAGES OF CARBOHYDRATE HYDROLYSIS - Kimsanova G.A.; Nematova M.T.; Eraliyeva G.A.; Topilova F (International Scientific and Current Research Conferences, 2024)
It is known that the period of transition from lactotrophic nutrition to definitive nutrition is critical in the life of mammals. At this time, significant changes take place in the quantity and quality of incoming nutrients, which determines the further course of development of the organism. [1, 2, 3]